2018
DOI: 10.1126/science.aar7204
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methane emissions from the U.S. oil and gas supply chain

Abstract: Methane emissions from the U.S. oil and natural gas supply chain were estimated by using ground-based, facility-scale measurements and validated with aircraft observations in areas accounting for ~30% of U.S. gas production. When scaled up nationally, our facility-based estimate of 2015 supply chain emissions is 13 ± 2 teragrams per year, equivalent to 2.3% of gross U.S. gas production. This value is ~60% higher than the U.S. Environmental Protection Agency inventory estimate, likely because existing inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
823
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 793 publications
(879 citation statements)
references
References 61 publications
49
823
7
Order By: Relevance
“…From the results of this study, we estimate emissions from UNG production and gathering facilities in SWPA to be equivalent to 0.5 ± 0.3% of production, in agreement with published top‐down emission estimates from northeast PA (0.36 ± 0.09%) and SWPA (0.0–3.5%) and site‐level measurements at well sites in northeast PA (0.44 ± 0.15%) and SWPA (0.57 ± 0.23%; Alvarez et al, ; Barkley et al, ; Omara et al, ; Ren et al, ). These emission rates as a percent of production are lower than rates found from top‐down studies performed in other gas basins, with the next lowest rate measured in the Haynesville shale at 1.3% (Alvarez et al, ; Karion et al, ; Peischl et al, ; Pétron et al, ; Schwietzke et al, ; Smith et al, ). The low fractional emission rates in this region are likely due to Marcellus wells having the highest production per well in the United States (Barkley et al, ; U.S. Energy Information Administration, ), requiring fewer components to produce large amounts of gas and thus lowering the potential for leaks (Brantley et al, ; Mitchell et al, ; Omara et al, ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From the results of this study, we estimate emissions from UNG production and gathering facilities in SWPA to be equivalent to 0.5 ± 0.3% of production, in agreement with published top‐down emission estimates from northeast PA (0.36 ± 0.09%) and SWPA (0.0–3.5%) and site‐level measurements at well sites in northeast PA (0.44 ± 0.15%) and SWPA (0.57 ± 0.23%; Alvarez et al, ; Barkley et al, ; Omara et al, ; Ren et al, ). These emission rates as a percent of production are lower than rates found from top‐down studies performed in other gas basins, with the next lowest rate measured in the Haynesville shale at 1.3% (Alvarez et al, ; Karion et al, ; Peischl et al, ; Pétron et al, ; Schwietzke et al, ; Smith et al, ). The low fractional emission rates in this region are likely due to Marcellus wells having the highest production per well in the United States (Barkley et al, ; U.S. Energy Information Administration, ), requiring fewer components to produce large amounts of gas and thus lowering the potential for leaks (Brantley et al, ; Mitchell et al, ; Omara et al, ).…”
Section: Resultssupporting
confidence: 89%
“…Recent atmospheric studies measuring CH 4 emissions from natural gas activities ranging from component‐level (Zavala‐Araiza et al, ) to entire gas production basins (Barkley et al, ; Peischl et al, ; Pétron et al, ; Schwietzke et al, ; Smith et al, ) to continental‐scale inversions of emission inventories (Schwietzke et al, ) have shown large discrepancies between atmospheric and inventory‐based approaches. Emission estimates from this broad range of work systematically find that the EPA consistently underestimates CH 4 emissions from natural gas systems (Alvarez et al, ; Brandt et al, ; Zavala‐Araiza et al, ). One reason for this discrepancy may relate to the presence of high emitters responsible for a skewed distribution of CH 4 emissions along the supply chain (Brandt et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Brandt et al (—see especially their Table S6) showed that in many U.S. gasfields and gas transmission and distribution systems, much of the mass of gas emitted comes from a few major leaks. Similarly, a recent synthesis of methane emissions from the oil and natural gas supply chain indicates that the most emissions come from production wells and that those are dominated by a few major sources (Alvarez et al, ). Mineral deposits provide a good analogy.…”
Section: Practical Emission Reduction and Removal—tractable Emissionsmentioning
confidence: 99%
“…The percentage is 1.9% if only production, gathering, and processing are included (Alvarez et al, ).…”
Section: Introductionmentioning
confidence: 99%